2003
DOI: 10.1038/sj.ejcn.1601631
|View full text |Cite
|
Sign up to set email alerts
|

Plasma thiols and their determinants in phenylketonuria

Abstract: Objective: Treatment of phenylketonuria (PKU) patients consists of a phenylalanine-restricted diet supplemented with a tyrosine-, vitamin-and oligoelement-enriched amino-acid mixture. Vitamins and oligoelements may be deficient when compliance with the supplemented special formula is poor. Plasma thiol concentrations (especially homocysteine) depend mainly on B-vitamin intake. Our aim was to evaluate the plasma thiol concentrations (homocysteine, cysteine and glutathione) and their determinants (methionine, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Numerous studies have provided experimental evidence demonstrating oxidative stress in human PKU patients and animal models (Artuch et al, 2001(Artuch et al, ,2004Colome et al, 2003;Ercal et al, 2002;Martinez-Cruz et al, 2002;Sierra et al, 1998;Sirtori et al, 2005). Our laboratory previously demonstrated increased inducible nitric oxide synthase production by infiltrative cd11b macrophage cells in the mesencephalon and hypothalamus of PKU mice (Embury et al, 2005), providing further evidence of oxidative processes occurring in these regions.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Numerous studies have provided experimental evidence demonstrating oxidative stress in human PKU patients and animal models (Artuch et al, 2001(Artuch et al, ,2004Colome et al, 2003;Ercal et al, 2002;Martinez-Cruz et al, 2002;Sierra et al, 1998;Sirtori et al, 2005). Our laboratory previously demonstrated increased inducible nitric oxide synthase production by infiltrative cd11b macrophage cells in the mesencephalon and hypothalamus of PKU mice (Embury et al, 2005), providing further evidence of oxidative processes occurring in these regions.…”
Section: Discussionmentioning
confidence: 86%
“…Ercal et al (2002) provided experimental evidence of oxidative damage in Pah enu2 mice that included increased concentration of the lipid peroxidation by-product malon-dialdehyde in brain tissue, decreased glutathione/glutathione disulfide also in brain and increased catalase and glucose-6-phosphate dehydrogenase in erythrocytes of these animals. Other studies indicating the role of oxidative stress in PKU include human studies by Artuch et al (2001Artuch et al ( , 2004; Colome et al (2003);and Sierra et al (1998). Sirtori et al (2005) demonstrated the involvement of oxidative stress in human PKU patients through increased levels of thiobarbituric acid reactive species (indicative of lipid peroxidation) and decreased total antioxidant reactivity, suggestive of deficient capacity to handle increases in reactive species.…”
Section: Discussionmentioning
confidence: 99%
“…While a higher dietary intake of natural folate is linked with reduced cancer risk (Duthie 2011;Figueiredo et al 2009), there are also reports that supplementation with synthetic folic acid actually increases cancer risk (Cole et al 2007;Wien et al 2012;Ebbing et al 2009;Figueiredo et al 2009), cancer mortality, and all-cause mortality (Ebbing et al 2009). Both high and low blood concentrations of folate and vitamin B12 have been reported in PKU patients compared to controls (Colome et al 2003;Huemer et al 2008;Schulpis et al 2002). Colomé et al found lower levels of homocysteine (hcy) concurrent with higher concentrations of folate and vitamin B12 (Colome et al 2003), while Schulpis et al found higher hcy levels and lower folate and vitamin B12 concentrations compared to controls (Huemer et al 2008;Schulpis et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Both high and low blood concentrations of folate and vitamin B12 have been reported in PKU patients compared to controls (Colome et al 2003;Huemer et al 2008;Schulpis et al 2002). Colomé et al found lower levels of homocysteine (hcy) concurrent with higher concentrations of folate and vitamin B12 (Colome et al 2003), while Schulpis et al found higher hcy levels and lower folate and vitamin B12 concentrations compared to controls (Huemer et al 2008;Schulpis et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…According to some authors, PKU and HPA patients may receive excessive amounts of vitamin B 12 and folate (40)(41)(42). The risks of possible side effects from such a status, and particularly in relation to tumor growth are often discussed in literature.…”
Section: Discussionmentioning
confidence: 99%